Ukuran Perusahaan Dan Likuiditas Terhadap Kualitas Laporan Keuangan Pada Perusahaan Property And Real Estate Yang Terdaftar Di Bursa Efek Indonesia Tahun 2018-2022 - sari, Laynita; Lasari, Mailona (JURNAL PUNDI, 2024)
This research aims to examine the influence of company size and liquidity on the quality of financial reports. The sampling technique used in this research is the purposive sampling method using criteria. The research sample is property and real estate companies listed on the Indonesia Stock Exchange from 2018-2022. Where the companies listed on the Indonesian Stock Exchange during the latest period, namely 2022, consist of 53 companies, with a total final sample of 45 companies during the 5 year research period. Data was collected using documentation and literature study methods. The data analysis technique used is the Classical Assumption Test and Hypothesis Testing using panel data regression using Eviews 9. The research results show that: (1) Company size has a positive and significant effect on the quality of financial reports, (2) Liquidity has a positive and significant effect on the quality financial statements.